Development of Disaster Mitigation Learning Materials through Forest Conservation Based on Local Wisdom Integrated with Merdeka Curriculum - Hidayah, Nurul; Arfan, Amal; Uca, Uca; Hasriyanti, Hasriyanti (Universitas Negeri Makassar, 2024)
This research was conducted using the Research and Development approach. The research aims to determine the development of disaster mitigation learning materials through forest conservation based on local wisdom integrated with the independent curriculum, determine the feasibility of disaster mitigation learning materials through forest conservation based on local wisdom integrated with the independent curriculum, and determine the effectiveness of disaster mitigation learning materials through forest conservation. Process To determine the feasibility of the product, the material / content expert test, language expert test and field practitioner validation test (subject teacher) were carried out. In addition, limited trials and large-scale trials were conducted on the research subjects, namely class XI IPS. The analysis used normality test, paired sample t-test and N-Gain test. The research instrument is a questionnaire and pretest-posttest questions to determine the improvement of students' understanding. The results showed that the product was in the valid category. The score obtained from the validation results of the material expert test was 90.62%, language validator 90.91%, practitioner 84.41% and limited scale test 86.51%. The large-scale test showed an increase in students' understanding in the moderate category after the implementation of learning using the material.